Pembuatan Aplikasi Delivery Order Bunga pada Toko X Berbasis Mobile - Kelvin Sanjaya; Kristo Radion Purba; Justinus Andjarwirawan (Jurnal Infra, 2017)
In this era, people want everything to be fast, easy and use less power. People nowadays are too lazy to go out. Because of this reason, a breakthrough which is an application of flower message delivery service was made. This application is based on Android, designed to use HTML 5, and is supported with a compilation by Phonegap. By using the application, with the internet being installed in the gadget on the Android operating system, this delivery service can be accessed more practical and very easy to use.This application makes people save more time and costs. The availability of the chat features simplify the complicated flower ordering especially in Surabaya where Google Map application is supported. This will also make people can check the position of their flower orders easily.